Stagecoach a classic rags-to-riches tale from the frontiers of capitalism - Wolmar, Christian (Orion Business Books, 1999)
The rise and rise of Stagecoach is an emblematic rags-to-riches story of the Conservative era of the 1980s and 1990s. This book tells the story of how the two founders, the brother and sister team of Brian Souter and Ann Gloag, emerged from humble beginnings on a bleak Perth council estate to become muliti-millionaires, worth over #300 million apiece. Based on exclusive interviews with Souter and other main players and critics, this is a story of one of the most unlikely successes